Pengaruh Metode Pembelajaran Bahasa Jawa Melalui Bermain Peran terhadap Perilaku Sopan Santun Anak - Atik Masruroh; Nurbiana Dhieni; Karnadi Karnadi (Universitas Mathla'ul Anwar Banten, 2020)
THE EFFECT OF JAVANESE LANGUAGE LEARNING METHODS THROUGH ROLE PLAYING ON CHILD POLITE BEHAVIOR. The purpose of this study was to examine how much influence the Javanese language learning method through playing macro roles and playing micro roles on the behavior of courtesy in grade 2 elementary school children in Lamongan Regency. The behavior of courtesy in this study is based on Javanese culture, focused on three aspects namely respecting older people, choosing the language level wisely, and obeying orders. This research was conducted at SDN Made IV and SDN Sukorejo II. This research was conducted in the odd semester of the 2019/2020 school year with a total of 68 research subjects. Data collection techniques using the method of observation. While the data analysis technique uses t-test, which has previously been tested for normality and homogeneity. The results showed that the average value of the experimental class was 58.24, while the control class was 56.5. From the results of the study found that the results of a significant value of 0.018 < 0.05. Then the results are obtained that there are differences in the average behavior of courtesy between children who are taught with the Javanese learning method through playing macro roles and children who are taught with the Javanese learning method through playing micro roles. Thus, the behavior of the children polite given the Javanese language learning method through playing macro roles is higher than the children who were given the Javanese learning method through micro role playing.